Load Rating of Al Halfaia Bridge over the Nile (Journal of Building and Road Research, 2021)
This paper summarizes the results of applying load rating process that has been applied to Halfaya Bridge over the main Nile in Khartoum, Sudan. Load rating procedures have reviewed as per Manual of Bridge Evaluationof AASHTO Standards. Three levels of H/Y live loadings have been considered. AASHTO HL-93 is used for design load rating. For Legal load rating the Sudanese legal loads - as per Sudan National Highway Authorityare considered. Permit load rating process has been made using actual special heavy truck used in Sudan during the last 20 years .The rating process has been made on the assumption that the capacity of the main structural element of the bridge, which is Girder type II Composite Steel Ibeams, had been decreased with different percentage from 10%up to 20%, due to different factors. Suitable software, CSi Bridge, has been used for calculations and the results are presented. The paper predicted the load rating factors for the composite steel I-beams of the bridge- moment and shear wise- for considerable capacity loss in future .The paper also checked the deflection of the composite I-Girder .Results showed that deflection is the governing factor when stiffness is lost by 8%, but still the momentcapacity is the governing factor –design load rating –when the loss is 5%of the capacity. Suggested several recommendations to save such vital structure are given
Keywords: bridge load rating; Al- Halfaia Bridge; AASHTO-LRFD